‘Conscience functioning and its developmental delays in Dutch female offenders’ - Verkade, Marion (The journal of forensic psychiatry & psychology, 2021)
According to the integrative theory of conscience, conscience is defined as a psychological function, consisting of interrelated and reciprocally influencing aspects: the capacity for empathy, the tendency to experience self-conscious emotions, and moral reasoning. Previous research in Dutch populations suggests that offenders have lower conscience functioning than non-offenders, but that female offenders may have fewer deficiencies than male offenders and that the underlying pattern may differ. However, little is known about the conscience of female offenders compared to non-offending women. In this study, conscience functioning of 38 Dutch female offenders was compared to that of 114 non-offending female controls, 77 from the general population and 37 with psychiatric problems. Offenders scored lower on affective empathy, showed stagnated self-centering, and made more use of self-serving cognitive distortions than both non-offending control groups, with medium to large effect sizes. Findings implicate that treatment programs should focus on learning to decentralize, mentalize, and self-regulate.